The influence of parametrics on the interior and its equipment in parametric buildings (Collection of scientific works «Scientific Problems of Architecture and Urban Planning» | ODABA, 2025)
The article highlights the issue of the emergence and formation of parametricism as a style in architecture and design. The features of the formation of the interior and its equipment in parametric buildings are considered. An analysis of the literature and various sources of research on parametricism is carried out. It is revealed that parametricism as a style has already been formed, although it is in a state of development and requires more active implementation in real design, as well as in the process of training a young architect. Developed computer technologies and programs for creating three-dimensional complex parametric forms are the basis and a unique opportunity for achievements in this direction. World practice shows that the parametric form of a building directly affects its internal environment, the interiors of the building, and subsequently the style of the interior, and its furniture and equipment. It is shown that parametric design opens up opportunities for creating unique architectural buildings, structures, and design objects that were previously impossible or very difficult to implement. Examples of existing buildings made in the parametric style using the latest design technologies are demonstrated. All models created by architects and designers using digital tools such as 3D modeling have certain features: length, width, depth, orientation and geometry. And design, in turn, is based on the relationship between functions, parts and drawings, and it is powered by imagination. 3D modeling tools such as: BIM (Building Information Modeling), CAD (ComputerAided Design), Parametric Design, Augmented Reality (AR), Generative Design, and others are analyzed. The use of these computer programs and applications in the work of an architect allows for more accurate calculation of the parameters of elements and their interaction with the environment.The demonstrated examples of existing interiors in the style of "parametric design" and furniture prove that when designing, computer technologies and the latest programs are used not only in architecture, but also in design. In addition, AI (artificial intelligence) is involved in the creation of the interior and its equipment, and this reality requires mastery and scientific understanding.
Keywords: parametricism; parametric design; interior; Parametric style; architecture; artificial intelligence (AI); Virtual Reality (VR); CAD; 3D modeling; innovative design